Study Of Zinc Oxide Nanostructures Grown On Ptfe Substrate By Chemical Bath Deposition For Photodetector Application - Farhat, Omar F A (2018)
This project devoted to study physical properties of ZnO nanostructure grown on PTFE flexible substrate by chemical bath deposition. A flexible substrate (PTFE, trade name Teflon) was introduced to grow ZnO nanostructure for the first time for obtaining a substrate with a high melting point to improve the crystallization of the material deposited on it by annealing process. This flexible substrate may enable new markets for large-area printed electronics or low-cost disposable devices. Using flexible substrates to fabricate electronic devices promises lower manufacturing costs because of the additive, non-vacuum nature of the technology.